2016
DOI: 10.1016/j.ijpharm.2016.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Age-appropriate and acceptable paediatric dosage forms: Insights into end-user perceptions, preferences and practices from the Children’s Acceptability of Oral Formulations (CALF) Study

Abstract: A lack of evidence to guide the design of age-appropriate and acceptable dosage forms has been a longstanding knowledge gap in paediatric formulation development. The Children's Acceptability of Oral Formulations (CALF) study captured end-user perceptions and practices with a focus on solid oral dosage forms, namely tablets, capsules, chewables, orodispersibles, multiparticulates (administered with food) and mini-tablets (administered directly into the mouth). A rigorous development and testing phase produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 49 publications
4
55
0
1
Order By: Relevance
“…Girls and female prescribers had a slightly higher association with the prescriptions of liquids. This was in accordance with previous studies that showed that women have greater difficulty swallowing solid formulations than men and that boys believe they can swallow larger solids than girls . The literature does not offer any explanation for these gender differences.…”
Section: Discussionsupporting
confidence: 91%
“…Girls and female prescribers had a slightly higher association with the prescriptions of liquids. This was in accordance with previous studies that showed that women have greater difficulty swallowing solid formulations than men and that boys believe they can swallow larger solids than girls . The literature does not offer any explanation for these gender differences.…”
Section: Discussionsupporting
confidence: 91%
“…An electronic questionnaire was built using the web‐based LimeSurvey version 2.06 (LimeSurvey GmbH, Hamburg, Germany). The questions were derived from sources regarding the manipulation of medicines for paediatric administration, such as the MODRIC guidelines, and additional research regarding manipulation of medication in children . Questions gave insight into the extent, reasons and methods of manipulation of oral dosage forms for children by parents and caregivers, and included six topics: demographic data, current medication, methods and reasons for manipulation, medication adherence in relation to manipulation, the possible combined administration of oral medicines and the sources of information consulted regarding manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that the paediatric use of off-label and unlicensed medicines are a reality and that there is a lack of medicines well studied for children. Although there are already some studies focusing on the perceptions of children [26][27][28], it is still important to improve our knowledge in this area. It is fundamental to develop research in order to understand attitudes and preferences of children and their caregivers with the aim of developing dosage forms and formulations which are children-friendly.…”
Section: Final Remarksmentioning
confidence: 99%